High-temperature-resistant lightweight aggregate rare earth oxide modified aluminum oxide hollow microspheres as well as preparation method and application thereof

By adding anionic dispersant to the grinding fluid of the oxide empty heart ball to improve the pillar potential of the powder particles, the spray granules are used to prepare the aluminum aluminum aluminum aluminum hollow micro -ball, which solves the crispy and decentralized alumina empty heart ball and the dispersion is not decentralized. The problem of ordinaryness has achieved efficient and stable hollow micro -ball preparation and improvement of material performance.

CN119371190APending Publication Date: 2025-01-28HANGZHOU RULIN NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411559310.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing hollow alumina sphere is brittle, poor toughness, high sintering temperature, and easy to damage, which limits its application. The spray granulation method has high requirements for the dispersion uniformity and stability of the slurry, and has not yet been successfully prepared for rare oxide earth modification. Hollow microspheres of alumina.

Method used

Use spray granules to prepare oxidation of rare earth aluminum aluminum oxide hollow microspheres. By adding an anion dispersant with COO-group to the grinding fluid, the pillar pillar potential is increased And burning at high temperature to form a hollow micro -ball.

Benefits of technology

The stable dispersing and efficient preparation of the aluminum oxide aluminum oxide aluminum oxide hollow microsphere is achieved, improved the spherical and compressive strength, reduced the thermal conductivity, enhanced the overall performance of the material, and was suitable for the fields of fire resistance and thermal insulation materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371190A_ABST
    Figure CN119371190A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant lightweight aggregate rare earth oxide modified aluminum oxide hollow microsphere as well as a preparation method and application thereof, and belongs to the field of refractory materials. The rare earth oxide modified aluminum oxide hollow microspheres are prepared by adopting a spray granulation method, and aluminum oxide and rare earth oxide mixed powder is subjected to sanding, spray granulation and high-temperature firing to prepare the rare earth oxide modified aluminum oxide hollow microspheres. The rare earth oxide is used as a modifier, and the properties of polarization characteristic, large volume, inhibition of crystal transformation of gamma-phase aluminum oxide at high temperature and the like of the rare earth oxide are utilized, so that the sintering temperature of the aluminum oxide hollow microspheres is reduced, sintering is promoted, crystal boundaries are purified, aluminum oxide crystal grains are refined, and cracks are passivated; the problems that aluminum oxide hollow microspheres are brittle, poor in toughness, high in sintering temperature, prone to damage and the like are solved, and the strength, toughness, hardness, density, wear resistance, corrosion resistance and other performance of the hollow microsphere shell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to high temperature resistant lightweight aggregate rare earth oxide modified alumina hollow microspheres and a preparation method and application thereof, belonging to the field of refractory materials. Background Art

[0002] Alumina hollow microspheres have the characteristics of light weight, low thermal conductivity, sound insulation, wear resistance, high dispersion, good electrical insulation and thermal stability. Alumina hollow microspheres are used for refractory insulation materials. They have low density and light weight, thermal shock resistance, good thermal insulation performance, low heat capacity, high compressive strength, high load softening temperature, low re-burning linear shrinkage, wear resistance, etc. It is a widely used lightweight, high-strength, high-temperature resistant hollow insulation material.

[0003] At present, the processes for preparing hollow alumina microspheres include slurry blowing, spray foaming, melt blowing, rolling ball method and spray granulation method. Patent CN101798230 B invented a method for preparing hollow alumina spheres toughened with zirconium oxide, which uses industrial alumina as the main raw material and adds zirconium-containing toughening materials. The process is carried out by melting and blowing in an arc furnace at a temperature of 2100-2500℃, and then sieved to obtain hollow alumina spheres toughened with zirconium oxide with a particle size of 0.2-5mm. The bulk density of the hollow spheres is 0.78-0.85g / cm 3 . Patent CN 101792317 B invented a method for preparing high-strength hollow alumina balls. Compared with the hollow alumina balls currently produced with pure industrial alumina, the hollow alumina balls have thicker ball walls and greatly improved compressive strength. The compressive strength of a single hollow alumina ball can be increased from 15.7N to 38N, and have better mechanical strength and higher operating temperature. The above two patented technologies are that alumina is melted in an arc furnace and then sprayed into balls, and the preparation process consumes a lot of energy. Patent CN114573012 B invented a bird's nest structure alumina and its preparation method and application. The bird's nest structure alumina is a hollow ball structure. There is a large hole that is concave inward on the hollow ball. The surface of the hollow ball is a network structure covered with fine holes. The particle size of the hollow ball is 10-80μm, the pore size of the large hole is 5-30μm, and the pore size of the fine hole is 30-200nm. This technology is to separate the precipitate from the dispersion and transport the suspension to the spray granulator to prepare hollow structure alumina. It fails to prepare a uniformly dispersed slurry, resulting in a low one-time yield, which is not conducive to industrial production. Meng Shanshan et al. reported the effect of dispersant on 99.8% high-purity alumina spray granulation powder. They selected an acrylic resin with an addition amount of 0.40% to 0.80% as a dispersant. The alumina prepared by spray granulation of the acrylic resin dispersed slurry has high sphericity and no defects. The particle size is about 45 to 150μm, and the loose density is 1.16g / cm 3When polycarboxylic acid ammonium salt and acrylic acid ammonium salt were used as dispersants, the obtained slurry showed apple-shaped defects after spray granulation, and the sphericity of the particles was not high.

[0004] At present, the hollow alumina spheres prepared by pure industrial alumina are brittle, have poor toughness, high sintering temperature, and are prone to breakage, which limit the application of hollow alumina spheres. Spray granulation has been reported to be used for the preparation of hollow spheres, but this method has high requirements for the dispersion uniformity and stability of the slurry. At present, there is no report on the successful preparation of rare earth oxide modified hollow alumina microspheres by spray granulation. Summary of the invention

[0005] In view of this, the purpose of the present invention is to overcome the deficiencies of the prior art and provide a high temperature resistant lightweight aggregate rare earth oxide modified alumina hollow microspheres and a preparation method and application thereof.

[0006] The applicant found that the technical key to the preparation of rare earth oxide modified alumina hollow microspheres is whether the rare earth oxide and alumina powders can be evenly dispersed in the slurry. The dispersion stability of the powders in the slurry is determined by their zeta potential. The higher the absolute value of the zeta potential (positive or negative), the more stable the dispersion system. In order to improve the zeta potential of the slurry, the selection of factors such as the particle size, content, dispersant and pH of the powder is the technical key to the preparation of a stably dispersed slurry. Only a highly dispersed slurry can be used to prepare a hollow structure material with high sphericity through a spray granulation method.

[0007] The invention adopts a spray granulation method to prepare rare earth oxide modified alumina hollow microspheres, which provides an industrialized production technology for the application of rare earth oxide modified alumina hollow microspheres in the fields of high-temperature lightweight refractory materials, thermal insulation materials and sound absorbing materials.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] The present invention first provides a method for preparing high temperature resistant lightweight aggregate rare earth oxide modified alumina hollow microspheres, which comprises the following steps:

[0010] 1) Deionized water and COO - The dispersant of the group is mixed, and then the aluminum oxide and rare earth oxide mixed powder are added and ground. During the grinding process, the pH value of the system is controlled to make COO - After the groups are completely dissociated and ground to the desired particle size, a binder is added to the grinding liquid, and after high-speed dispersion, the slurry required for spray granulation is obtained;

[0011] 2) The slurry is uniformly conveyed to a spray granulator, the hollow microspheres are collected in a collector, and then burned to obtain rare earth oxide modified alumina hollow microspheres.

[0012] According to some embodiments of the present invention, the dispersant in step 1) is one of ammonium polyacrylate and ammonium polymethacrylate, and the pH of the system is maintained at 8.5-9.5 during the grinding process so that COO in the dispersant - The groups dissociate completely.

[0013] According to some embodiments of the present invention, grinding to a desired particle size in step 1) means grinding until the particle size of the powder in the grinding liquid is less than 500 nm.

[0014] According to some embodiments of the present invention, the aluminum oxide in step 1) refers to industrial grade aluminum oxide, and the purity of aluminum oxide is above 99%; the rare earth oxide refers to La2O3, CeO2, La 0.36 Ce 0.64 O 1.82 and La2Ce2O7; in the mixed powder, the mass percentage of aluminum oxide is 97%-98%.

[0015] According to some embodiments of the present invention, in step 1), the mass ratio of the mixed powder to the dispersant is 1:0.001; the mass ratio of deionized water to the dispersant is 0.5-1:0.001; and the mass ratio of the dispersant to the binder is 1:20.

[0016] According to some embodiments of the present invention, in step 1), the binder is polyvinyl alcohol (PVA).

[0017] According to some embodiments of the present invention, in step 2), the inlet temperature of the spray granulator is controlled at 140°C-180°C, and the burning temperature is 1200°C-1500°C.

[0018] The present invention also provides a rare earth oxide modified alumina hollow microsphere prepared by the method, wherein the rare earth oxide modified alumina hollow microsphere has a bulk density of 0.82-0.86 g / cm 3 , particle size D 50 The wall thickness is 25-35μm, the wall thickness is 200-500nm, the compressive strength is 9-12MPa, and the room temperature thermal conductivity is 0.2-0.3W / (m·K).

[0019] The invention also provides application of the rare earth oxide modified alumina hollow microspheres as refractory heat-insulating materials.

[0020] Compared with the prior art, the beneficial effects of the present invention include:

[0021] 1) In order to improve the dispersion of the mixed powder of aluminum oxide and rare earth oxide in the grinding liquid, the present invention adds a - The anionic dispersant of the COO group increases the surface zeta potential of the powder due to its dissociation and adsorption characteristics in the grinding liquid, and the electrostatic repulsion between particles is enhanced.- The steric hindrance of the anionic dispersant molecular chain of the group makes the adsorption between particles relatively weakened. The electrostatic stabilization and steric stabilization mechanism of the anionic dispersant effectively eliminates the weak agglomeration phenomenon in the grinding liquid, improves the fluidity of the powder particles, reduces the viscosity of the grinding liquid, and obtains a stable and uniformly dispersed grinding liquid. - When the pH of the anionic dispersant in the grinding liquid is greater than 8.5, COO - The groups are completely dissociated, and the pH value of the grinding liquid is adjusted to 8.5-9.5. At this time, the repulsive force between the particles is the largest, and the powder particles are evenly and stably dispersed in the grinding liquid, ensuring the uniform distribution of alumina and rare earth oxide components in the spray granulation slurry.

[0022] 2) Since the maximum saturation capacity of the powder adsorbing the dispersant decreases with the increase of pH, when the pH value of the grinding liquid is 8.5-9.5, the surface charge of the particles is negative, and COO - The groups are completely dissociated, so the adsorption of dispersants on the particle surface only occurs on a few positive sites, and the saturation capacity of particles to adsorb dispersants is low; when an excess amount of dispersant is added, the excess dispersant enhances the ionic strength in the grinding liquid and the "linkage" effect on the powder particles, thereby strengthening the interaction between the powder particles, increasing the viscosity of the grinding liquid, and destroying the stability of the grinding liquid, so the present invention controls the amount of dispersant added.

[0023] 3) The present invention selects polyvinyl alcohol as a binder. Polyvinyl alcohol is a non-ionic polymer and is adsorbed on the surface of powder particles in the form of adsorption. There is cohesive force between the adsorbed molecules to form a thin film, which has the effect of reducing friction. An appropriate amount of polyvinyl alcohol forms a very thin lubricating film on the surface of the powder particles, which reduces the flow resistance of the powder particles and improves the dispersibility of the powder. During the spray drying process of the slurry with good dispersibility, due to the action of capillary force, the particles and the binder migrate to the surface of the droplets and form a rigid shell on the surface of the droplets, resulting in the formation of hollow particles.

[0024] 4) The present invention uses a spray granulation method to prepare the rare earth oxide modified alumina hollow microspheres. During the high-temperature calcination process, the polarization characteristics of the rare earth oxide reduce the activation energy of the alumina powder reaction, thereby reducing the sintering temperature. Since the calcination temperature is 800°C-1200°C to generate REAlO3 (RE = La, Ce), the calcination temperature is 1500°C to generate REAl 11 O 18 , REAlO3 has high temperature stability and oxidation resistance. The introduction of REAlO3 into alumina improves the sintering behavior and thermal shock stability of alumina hollow microspheres; REAl 11 O 18 It is a thermal barrier material with high hardness, high thermal stability, high infrared emissivity and low thermal conductivity. 11 O18 Compared with pure alumina hollow microspheres, the rare earth oxide modified alumina hollow microspheres have lower thermal conductivity and improved the overall performance of the material. Rare earth oxide modified alumina hollow microspheres will have broad application prospects as high temperature resistant lightweight aggregates in refractory materials.

[0025] 5) Lanthanum oxide and cerium oxide can inhibit the crystallization of γ-phase alumina at high temperature. At a high temperature of 1100°C, a large amount of α-phase alumina appears in the unmodified alumina, only a small amount of α-phase alumina appears in the alumina modified with cerium oxide, and almost no α-phase alumina appears in the alumina modified with lanthanum oxide. Since lanthanum oxide and cerium oxide cover the surface of alumina particles, they protect some hydroxyl groups, prevent the sintering of alumina particles, delay the crystallization process of alumina, and improve the high-temperature stability of alumina.

[0026] 6) The rare earth oxide and alumina mixed powder concentration in the slurry prepared by the present invention is high, which reduces the evaporation of water during the spray granulation process, increases the ability to produce hollow microspheres, and reduces energy consumption; the prepared rare earth modified alumina hollow microspheres can adjust the rare earth oxide addition amount and the burning temperature according to different application fields, and can prepare high porosity hollow microspheres and dense shell hollow microspheres. In addition, the present invention adopts spray granulation technology to prepare rare earth oxide modified alumina hollow microspheres, which has simple production process, green environmental protection, low production cost, and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the SEM image of La2O3 modified alumina hollow microspheres prepared in Example 1 of the present invention.

[0028] Figure 2 This is the SEM image of CeO2 modified alumina hollow microspheres prepared in Example 2 of the present invention.

[0029] Figure 3 La prepared in Example 3 of the present invention 0.36 Ce 0.64 O 1.82 SEM image of modified alumina hollow microspheres.

[0030] Figure 4 This is the SEM image of La2Ce2O7 modified alumina hollow microspheres prepared in Example 4 of the present invention.

[0031] Figure 5 The La prepared in Comparative Example 3 of the present invention 0.36 Ce 0.64 O 1.82 SEM image of modified alumina hollow microspheres. DETAILED DESCRIPTION

[0032] The present invention is further described and illustrated below in conjunction with specific embodiments. The embodiments are merely exemplary of the present disclosure and do not define the scope of limitation. The technical features of each embodiment of the present invention may be combined accordingly without conflicting with each other.

[0033] Example 1

[0034] (1) Preparation of alumina and La2O3 mixed powder slurry: 100 L of deionized water and 0.1 kg of ammonium polyacrylate were added to a sand mill dispersion tank. After stirring and dispersing evenly, the sand mill was turned on and 97 kg of alumina and 3 kg of La2O3 powder were gradually added. The pH value of the grinding liquid was controlled at 8.5 during the grinding process. When the powder particle size in the grinding liquid was less than 500 nm, the grinding was stopped and the grinding liquid was input into a spray granulation dispersion tank. 2 kg of PVA was added and after high-speed dispersion, a spray granulation slurry containing 49.48% of alumina and La2O3 mixed powder was obtained.

[0035] (2) Preparation of La2O3-modified alumina hollow microspheres: The spray granulator was turned on, and the inlet temperature was controlled at 170°C. The slurry was uniformly conveyed into the spray granulator, and the hollow microspheres were collected in a collector. The hollow microspheres were then calcined at 1500°C to obtain La2O3-modified alumina hollow microspheres. Figure 1 3 is a SEM image of La2O3 modified alumina hollow microspheres. It can be seen from the image that the surface of the La2O3 modified alumina hollow microspheres obtained by the present invention is smooth and flat, the spherical particles are monodisperse, and no collapse or breakage is observed.

[0036] The obtained La2O3 modified alumina hollow microspheres were characterized, and the bulk density was tested by the measuring cylinder method, the particle size was tested by BT-9300ST laser particle size analyzer, the wall thickness was tested by focused ion beam scanning electron microscope, the compressive strength was tested by powder compressive strength test method (GB / T-43091-2023), and the room temperature thermal conductivity was tested by Hot Disk method / transient flat plate heat source method.

[0037] (3) Index: The bulk density of the La2O3-modified alumina hollow microspheres prepared in Example 1 is 0.86 g / cm 3 , particle size D 50 The wall thickness is 30.2μm, the wall thickness is 206nm, the compressive strength is 11.5Mpa, and the room temperature thermal conductivity is 0.22W / (m·K).

[0038] Example 2

[0039] (1) Preparation of alumina and CeO2 mixed powder slurry: 100 L of deionized water and 0.2 kg of ammonium polymethyl acrylate were added to a sand mill dispersion tank. After stirring and dispersing evenly, the sand mill was turned on and 196 kg of alumina and 4 kg of CeO2 powder were gradually added. The pH value of the grinding liquid was controlled at 9 during the grinding process. When the powder particle size in the grinding liquid was less than 500 nm, the grinding was stopped and the grinding liquid was input into a spray granulation dispersion tank. 4 kg of PVA was added. After high-speed dispersion, a spray granulation slurry containing 65.75% of alumina and CeO2 mixed powder was obtained.

[0040] (2) Preparation of CeO2 modified alumina hollow microspheres: The spray granulator was turned on, the inlet temperature was controlled at 140°C, the slurry was uniformly conveyed into the spray granulator, the hollow microspheres were collected in a collector, and then calcined at 1200°C to obtain CeO2 modified alumina hollow microspheres. Figure 2 3 is a SEM image of CeO2 modified alumina hollow microspheres. It can be seen from the image that the surface of the CeO2 modified alumina hollow microspheres obtained by the present invention is smooth and flat, the spherical particles are monodisperse, and no collapse or breakage is observed.

[0041] The obtained CeO2 modified alumina hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0042] (3) Index: The bulk density of CeO2-modified alumina hollow microspheres prepared in Example 2 is 0.85 g / cm 3 , particle size D 50 The wall thickness is 28.3 μm, the wall thickness is 480 nm, the compressive strength is 11.7 MPa, and the room temperature thermal conductivity is 0.28 W / (m·K).

[0043] Example 3

[0044] (1) Alumina and La 0.36 Ce 0.64 O 1.82 Preparation of mixed powder slurry: Add 100L deionized water and 0.15kg ammonium polymethacrylate into the sand mill dispersion tank, stir and disperse evenly, then turn on the sand mill and gradually add 146.25kg alumina and 3.75kg La 0.36 Ce 0.64 O 1.82 The pH value of the grinding liquid was controlled at 9.5 during the grinding process. When the particle size of the powder in the grinding liquid was less than 500nm, the grinding was stopped. The grinding liquid was input into the spray granulation dispersion tank, and 3kg of PVA was added. After high-speed dispersion, a granulated powder containing 59.25% of aluminum oxide and La was obtained. 0.36 Ce 0.64 O 1.82 Mixed powder spray granulation slurry.

[0045] (2)La 0.36 Ce 0.64 O 1.82 Preparation of modified alumina hollow microspheres: Turn on the spray granulator, control the inlet temperature at 150°C, transport the slurry to the spray granulator at a uniform speed, collect the hollow microspheres in the collector, and then calcine at 1300°C to obtain La 0.36 Ce 0.64 O 1.82 Modified alumina hollow microspheres. Figure 3 For La 0.36 Ce 0.64 O 1.82 The SEM image of the modified alumina hollow microspheres shows that the La 0.36 Ce 0.64 O 1.82 The surface of the modified alumina hollow microspheres is smooth and flat, and the spherical particles are monodispersed without collapse or breakage.

[0046] For the income 0.36 Ce 0.64 O 1.82 The modified alumina hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0047] (3) Index: La prepared in Example 3 0.36 Ce 0.64 O 1.82 The bulk density of modified alumina hollow microspheres is 0.82g / cm 3 , particle size D 50 The wall thickness is 32.8 μm, the wall thickness is 330 nm, the compressive strength is 9.3 MPa, and the room temperature thermal conductivity is 0.27 W / (m·K).

[0048] Example 4

[0049] (1) Preparation of mixed powder slurry of aluminum oxide and La2Ce2O7: 100 L of deionized water and 0.18 kg of ammonium polyacrylate were added to a sand mill dispersion tank. After stirring and dispersing evenly, the sand mill was turned on and 175.86 kg of aluminum oxide and 4.14 kg of La2Ce2O7 powder were gradually added. The pH value of the grinding liquid was controlled at 9 during the grinding process. When the particle size of the powder in the grinding liquid was less than 500 nm, the grinding was stopped and the grinding liquid was input into a spray granulation dispersion tank. 3.6 kg of PVA was added and after high-speed dispersion, a mixed powder spray granulation slurry containing 63.43% of aluminum oxide and La2Ce2O7 was obtained.

[0050] (2) Preparation of La2Ce2O7 modified alumina hollow microspheres: The spray granulator was turned on, the inlet temperature was controlled at 180°C, the slurry was uniformly conveyed into the spray granulator, the hollow microspheres were collected in a collector, and then calcined at 1400°C to obtain La2Ce2O7 modified alumina hollow microspheres. Figure 4 : This is a SEM image of La2Ce2O7 modified alumina hollow microspheres. It can be seen from the image that the surface of the La2Ce2O7 modified alumina hollow microspheres obtained by the present invention is smooth and flat, the spherical particles are monodisperse, and no collapse or breakage is observed.

[0051] The obtained La2Ce2O7 modified alumina hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0052] (3) Index: The bulk density of the La2Ce2O7 modified alumina hollow microspheres prepared in Example 4 is 0.83 g / cm 3 , particle size D 50 The wall thickness is 27.8 μm, the wall thickness is 220 nm, the compressive strength is 9.2 MPa, and the room temperature thermal conductivity is 0.23 W / (m·K).

[0053] Comparative Example 1

[0054] (1) Preparation of alumina slurry: 100 kg of alumina replaces 97 kg of alumina and 3 kg of La2O3 powder, and the rest is the same as in Example 1 (1).

[0055] (2) Preparation of hollow alumina microspheres: same as (2) in Example 1.

[0056] The obtained alumina hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0057] The hollow microspheres prepared in Comparative Example 1 and Example 1 have the same appearance. The obtained hollow microspheres have smooth and flat surfaces, the spherical particles are monodispersed, no collapse or breakage is observed, and the particle size and wall thickness of the hollow microspheres are similar. However, compared with Comparative Example 1, the bulk density of the hollow microspheres in Example 1 is increased by 1.7%, the room temperature thermal conductivity is reduced by 26.65%, and the compressive strength is increased by 3.2%; because at the calcination temperature of 1500°C, La2O3 reacts with Al2O3 to generate LaAl 11 O 18 , LaAl 11 O 18 It is a thermal barrier insulation material with a thermal conductivity of 0.8-2.6W / (m·K), which is significantly lower than that of alumina. In addition, the generated LaAl 11 O 18Located at the alumina grain boundary in the hollow microsphere shell, it inhibits the abnormal growth of alumina grains and promotes the densification of the alumina shell, thereby improving the compressive strength of the hollow microsphere.

[0058] Comparative Example 2

[0059] (1) Preparation of alumina slurry: 200 kg alumina replaces 196 kg alumina and 4 kg CeO2 powder, and the rest is the same as in Example 2 (1).

[0060] (2) Preparation of hollow alumina microspheres: same as (2) in Example 2.

[0061] The obtained alumina hollow microspheres were characterized using the same characterization and testing methods as in Example 1.

[0062] Example 2 compared with Comparative Example 2: The compressive strength of Example 2 is improved by 3.6% compared with Comparative Example 2. When the CeO2-modified alumina hollow microspheres in Example 2 are calcined at a temperature of 1000°C, CeO2 reacts with Al2O3 to form low-melting point compounds such as CeAlO3 and Al2Ce4O9. These low-melting point compounds tend to form a liquid phase on the surface of the particles. The generated liquid phase improves the wettability of the particles, fills the pores between the particles, and enhances the bonding and density between the particles in the shell layer of the hollow microspheres, thereby improving the compressive strength; while in the shell layer of the alumina hollow microspheres in Comparative Example 2, less liquid phase is generated by the particles, and the bonding between the particles is weaker, resulting in lower compressive strength. Therefore, adding rare earth oxide can reduce the sintering temperature of the alumina hollow microspheres.

[0063] Comparative Example 3

[0064] (1) Alumina and La 0.36 Ce 0.64 O 1.82 Preparation of mixed powder slurry: 0.23 kg of ammonium polymethacrylate replaces 0.15 kg of ammonium polymethacrylate, and the rest is the same as in Example 3 (1).

[0065] (2)La 0.36 Ce 0.64 O 1.82 Preparation of modified alumina hollow microspheres: the same as in Example 3 (2).

[0066] Figure 5 Comparative Example La of the present invention 0.36 Ce 0.64 O 1.82 SEM image of modified alumina hollow microspheres. 0.36 Ce 0.64 O 1.82Some of the modified alumina hollow microspheres have craters on their surface. If the amount of dispersant ammonium methacrylate is further increased, alumina particles with a bird's nest structure similar to that of the invention in patent CN114573012 B will appear, indicating that the amount of dispersant added is important for obtaining hollow microspheres with good performance.

[0067] The above embodiments show that the rare earth oxide modified alumina hollow microspheres obtained in the embodiments have the characteristics of low density and light weight, thermal shock resistance, good thermal insulation performance, low heat capacity, high compressive strength, high load softening temperature, low re-firing linear shrinkage, wear resistance, etc., can be used as refractory insulation materials, and have the characteristics of wide application, light weight, high strength and high temperature resistance.

[0068] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing high temperature resistant lightweight aggregate rare earth oxide modified alumina hollow microspheres, characterized in that: The method comprises the following steps: 1) Deionized water and COO - The dispersant of the group is mixed, and then the aluminum oxide and rare earth oxide mixed powder are added and ground. During the grinding process, the pH value of the system is controlled to make COO - After the groups are completely dissociated and ground to the desired particle size, a binder is added to the grinding liquid, and after high-speed dispersion, the slurry required for spray granulation is obtained; 2) The slurry is uniformly conveyed to a spray granulator, the hollow microspheres are collected in a collector, and then burned to obtain rare earth oxide modified alumina hollow microspheres.

2. The preparation method according to claim 1, characterized in that: In step 1), the dispersant is one of ammonium polyacrylate and ammonium polymethacrylate, and the pH of the system is maintained at 8.5-9.5 during the grinding process to allow the COO in the dispersant to - The groups dissociate completely.

3. The preparation method according to claim 1, characterized in that: Grinding to a desired particle size in step 1) means grinding until the particle size of the powder in the grinding liquid is less than 500 nm.

4. The preparation method according to claim 1, characterized in that: In step 1), the aluminum oxide refers to industrial grade aluminum oxide with a purity of more than 99%; the rare earth oxide refers to La2O3, CeO2, La 0.36 Ce 0.64 O 1.82 and La2Ce2O7; in the mixed powder, the mass percentage of aluminum oxide is 97%-98%.

5. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of the mixed powder to the dispersant is 1:0.001; the mass ratio of deionized water to the dispersant is 0.5-1:0.001; and the mass ratio of the dispersant to the binder is 1:

20.

6. The preparation method according to claim 1, characterized in that: In step 1), the binder is polyvinyl alcohol.

7. The preparation method according to claim 1, characterized in that: In step 2), the inlet temperature of the spray granulator is controlled at 140°C-180°C.

8. The preparation method according to claim 1, characterized in that: In step 2), the calcination temperature is 1200°C-1500°C.

9. A rare earth oxide modified alumina hollow microsphere prepared by the method according to any one of claims 1 to 8, characterized in that: The loose packing density of the rare earth oxide modified alumina hollow microspheres is 0.82-0.86 g / cm 3 , particle size D 50 The wall thickness is 25-35μm, the wall thickness is 200-500nm, the compressive strength is 9-12MPa, and the room temperature thermal conductivity is 0.2-0.3W / (m·K).

10. Use of the rare earth oxide modified alumina hollow microspheres as claimed in claim 9 as refractory heat-insulating materials.

Citation Information

Patent Citations

  • Method for producing high-strength alumina hollow spheres

    CN101792317B

  • Preparation method of zirconium oxide toughening aluminum oxide hollow balls

    CN101798230B

  • A bird's nest-like structure of alumina, its preparation method and application

    CN114573012B

  • Hollow proppants and a process for their manufacture

    US4547468A

Cited By

  • Ceramic blank with low shrinkage rate as well as preparation method and application thereof

    CN122102666A

  • Ceramic green body with low shrinkage and preparation method and application thereof

    CN122102666B